The challenge of comparing crop imagery over space and time - Hall, Ola; Archila Bustos, Maria Francisca (Technical Centre for Agricultural and Rural Cooperation, 2016)
Imagery collected by drones can help agricultural experts identify the causes of low crop productivity. But the technology must be adapted to determine different crop varieties from multispectral images. And problems of image calibration must be resolved.